2017
DOI: 10.1007/s13346-017-0408-1
|View full text |Cite
|
Sign up to set email alerts
|

Silica microparticles for sustained zero-order release of an anti-CD40L antibody

Abstract: Silica microparticle hydrogel depot (HG) formulation was prepared using spray drying of silica-based sol-gels for the sustained delivery of MR1 antibody which binds to CD40 ligand (CD40L). The formulation was tested in vitro for antibody release, surface morphology, particle size, rheology, and injectability. In vivo pharmacokinetic evaluation was performed for the microparticle formulation and free MR1 antibody in BALB/c female mice. Serum samples up to day 62 were assessed using an enzyme-linked immunosorben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…By plotting the cumulative release of triptorelin as a function of cumulative silica degradation, the function is linear and therefore the release rate of triptorelin is constant for 7 days in sink conditions. Tyagi et al have reported similar properties for an equivalent silica microparticle-silica hydrogel system that was developed for subcutaneous dosing of a therapeutic monoclonal antibody [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By plotting the cumulative release of triptorelin as a function of cumulative silica degradation, the function is linear and therefore the release rate of triptorelin is constant for 7 days in sink conditions. Tyagi et al have reported similar properties for an equivalent silica microparticle-silica hydrogel system that was developed for subcutaneous dosing of a therapeutic monoclonal antibody [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…The resulting depot is an injectable particle-reinforced composite, where the silica microparticles are joined together by silica nanoparticles to form a stable three-dimensional gel structure that flows when sheared. It has also been shown that properties of this type of silica-based composite can be adjusted to result in zero-order release [ 15 ]. The silica-based composite is non-flowing and stable at rest (preventing sedimentation of microparticles), but injectable as shear force is applied (e.g., during injection).…”
Section: Introductionmentioning
confidence: 99%
“…The biodegradation process does not change the pH within silica gel or in the surrounding tissue, in contrast to other commonly used polymeric LAI technologies. Further, it has been shown that the silica matrix is chemically and physically compatible with small molecules, monoclonal antibodies, peptides, and proteins. …”
Section: Introductionmentioning
confidence: 99%
“…Results confirm that PEGylation does not alter the shape of CNPs and significantly reduces the protein adsorption while maintaining their antioxidant properties, cytocompatibility, and rod-shaped CNPs exhibit superior ROS scavenging properties. The work from Tyagi et al evaluates the potential of subcutaneously administered dosing silica MPs on the surface morphology, particle size, rheology, injectability, and sustained delivery of an anti-CD40L antibody [9]. The intrinsic drawbacks of PLGA and poly(L-lactide) (PLA)-based polymeric delivery vehicles are the incomplete/burst release or instability of biologics that primarily results from the acidic environment created by the free lactic/glycolic acids.…”
mentioning
confidence: 99%